Hydrogen production from supercritical water gasification of lignin catalyzed by Ni supported on various zeolites. (1st July 2022) - Yu, Lihui; Zhang, Rui; Cao, Changqing; Liu, Lanjun; Fang, Jiabin; Jin, Hui
Graphical abstract: Highlights: The property and influence of Ni supported on 5 zeolites on SCWG of lignin were studied. The order of catalytic activity on SCWG: Ni/4A > Ni/3A > Ni/5A > Ni/13X > Ni/ZSM-5. The superiority of type-A zeolites over ZSM-5 as Ni support was the proper-size pores. H2 yield was increased by 1.9 times with catalysis of 30 wt% Ni loaded on 4A zeolite. Abstract: In the present study, supercritical water gasification of dealkaline lignin catalyzed by Ni supported on different zeolites (3A, 4A, 5A, 13X and ZSM-5) was investigated. Scanning electron microscopy-energy dispersive X‐ray spectrometry (SEM-EDS), N2 adsorption–desorption and X-ray diffraction (XRD) were used to characterize the catalyst. Most of these catalysts enhanced the gasification except Ni/ZSM-5, and the order of their catalytic activity was: Ni/4A > Ni/3A > Ni/5A > Ni/13X > Ni/ZSM-5. The higher activity of Ni/4A was probably because it has mesopores with proper size to disperse Ni and provide more active sites for the reaction. With the catalysis of Ni/4A, the hydrogen selectivity was increased from 27.07% to 42.61%, and the H2 yield increased from 3.14 mol/kg to 5.63 mol/kg. With Ni/4A, the prolongation of reaction time improved the gasification efficiency and hydrogen production, but its impact became less pronounced when it was above 20 min. The increase of the Ni loading amount from 0 to 30 wt% in Ni/4A improved the hydrogen yield by 1.9 times to 6.2 mol/kg, but its further increase from 30 wt% to 50 wt% had less influence.